2009
DOI: 10.1093/nar/gkp1071
|View full text |Cite
|
Sign up to set email alerts
|

Lin28-mediated post-transcriptional regulation of Oct4 expression in human embryonic stem cells

Abstract: Lin28 acts as a repressor of microRNA processing and as a post-transcriptional regulatory factor for a subset of mRNAs. Here we report that in human embryonic stem cells Lin28 facilitates the expression of the pivotal pluripotency factor Oct4 at the post-transcriptional level. We provide evidence that Lin28 binds Oct4 mRNA directly through high affinity sites within its coding region and that an interaction between Lin28 and RNA helicase A (RHA) may play a part in the observed regulation. We further demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
235
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(250 citation statements)
references
References 31 publications
15
235
0
Order By: Relevance
“…The co-expression of Lin28 and Oct4 in a sub-population of high-grade ovarian cancer cells is particularly intriguing, given that both genes have critical roles in the maintenance of pluripotency, and hence the production of induced pluripotent stem cells (Yu, et al, 2007;Heo et al, 2009;Pei, 2009). Importantly, we have found that Lin28 specifically binds to Oct4 mRNA and stimulates its translation in both human ES cells and embryonic carcinoma PA-1 cells (Qiu et al, 2009). This may explain, at least in part, the observed synergistic effects of the Lin28/Oct4 double-knockdown in the tumor cells (Figure 4e).…”
Section: Sub-population Of Eoc Cells Co-expresses Lin28 and Oct4mentioning
confidence: 86%
See 1 more Smart Citation
“…The co-expression of Lin28 and Oct4 in a sub-population of high-grade ovarian cancer cells is particularly intriguing, given that both genes have critical roles in the maintenance of pluripotency, and hence the production of induced pluripotent stem cells (Yu, et al, 2007;Heo et al, 2009;Pei, 2009). Importantly, we have found that Lin28 specifically binds to Oct4 mRNA and stimulates its translation in both human ES cells and embryonic carcinoma PA-1 cells (Qiu et al, 2009). This may explain, at least in part, the observed synergistic effects of the Lin28/Oct4 double-knockdown in the tumor cells (Figure 4e).…”
Section: Sub-population Of Eoc Cells Co-expresses Lin28 and Oct4mentioning
confidence: 86%
“…It has been shown to block the processing of let-7 microRNAs (Heo et al, 2008;Newman et al, 2008;Rybak et al, 2008;Viswanathan et al, 2008) as well as a handful of other microRNAs (Heo et al, 2009;Trabucchi et al, 2009). In addition, Lin28 has been reported by us and others to bind to a specific subset of mRNAs, including those for IGF-2, Oct4, and several cell cycle-related factors, thereby modulating their translation (Polesskaya et al, 2007;Qiu et al, 2009;.…”
Section: Introductionmentioning
confidence: 94%
“…7A). Because it has been demonstrated that LIN28A binds to polysomes and stimulates the translation of LIN28A-binding mRNAs (7,(23)(24)(25)(27)(28)(29), we also tested whether the increase in LIN28A led to an increase in the level of these cell cycle-associated proteins, by comparing the expression of CDK2, CDC2, and CDC20 proteins between control and LIN28A knockdown cells. Using Western blots, we showed that blocking endogenous LIN28A expression in A2780 and IGROV1 cells remarkably reduced the levels of CDK2, CDC2, and CDC20 proteins (Fig.…”
Section: Lin28a Promotes Cancer Cell Growth In Vitro and In Vivo-mentioning
confidence: 99%
“…This finding has been successfully phenocopied in a transgenic mouse model with an inducible LIN28A gene (21). Increasing evidence suggests that LIN28 may also be a master regulator controlling the pluripotency of embryonic stem (ES) 4 cells (22)(23)(24)(25). LIN28A, together with OCT4, SOX2, and NANOG (the "reprogramming factors"), can reprogram somatic cells to induced pluripotent stem cells (26).…”
mentioning
confidence: 94%
“…[2][3][4] A recently study showed that in mouse, LIN28 is essential to the development of primordial germ cells and may be involved in the malignant transformation of germ cells. 5 The expression of LIN28 was also found in human testicular germ cell tumors in a tissue microarray study with a limited number of cases.…”
mentioning
confidence: 99%